Perspectives for agronomy : adopting ecological principles and managing resource use : proceedings of the 4th Congress of the European Society for Agronomy, Veldhoven and Wageningen, the Netherlands, 7-11 July 1996 /: proceedings of the 4th Congress of the European Society for Agronomy, Veldhoven and Wageningen, the Netherlands, 7-11 July 1996. (1997) - Unknown
No abstract available